2012
DOI: 10.1111/j.1751-0813.2011.00878.x
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and efficacy of a novel doxorubicin and carboplatin chemotherapy protocol for the treatment of canine appendicular osteosarcoma following limb amputation

Abstract: This chemotherapy protocol did not result in a longer time to disease recurrence or OST in this population of dogs. Dual-agent protocols have failed to improve survival times and therefore we conclude that a single-agent protocol using carboplatin may be equally effective with less toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
1
19
1
Order By: Relevance
“…; Lane et al . ). In dogs, IL‐2 has been shown to have clinical efficacy against soft tissue sarcomas and osteosarcoma (Mengesha et al .…”
Section: Introductionmentioning
confidence: 97%
“…; Lane et al . ). In dogs, IL‐2 has been shown to have clinical efficacy against soft tissue sarcomas and osteosarcoma (Mengesha et al .…”
Section: Introductionmentioning
confidence: 97%
“…doxorubicin and platinum compounds (reviewed in [24]). Current therapeutic development for canine osteosarcoma involves the modification of current protocols and Standard of Care (SOC) agents with limited success [43], rather than the integration of new therapeutic agents as single or combinational therapy. Personalized medicine strategies provide an opportunity to expand a patient’s “therapeutic opportunities” by examining the molecular/biological factors that are fundamental to that individual’s disease etiology and progression.…”
Section: Discussionmentioning
confidence: 99%
“…As Dr Jacobs states, the AUSVETPLAN manual for equine influenza has been updated subsequent to the 2007/2008 outbreak. 2 The critical issue with regard to vaccination will be access to adequate quantities of an appropriate vaccine. At this stage, the respective horse-owning organisations have not established improved access to an emergency supply of vaccines should the need arise.…”
Section: Re: Equine Influenza Supplementmentioning
confidence: 99%
“…The second paper is a retrospective study of the efficacy and toxicity of a post-amputation chemotherapy protocol for appendicular osteosarcoma that comprises two initial doses of doxorubicin, followed by four doses of carboplatin. 2 Although numerous randomised trials have been performed in human oncology, canine treatment is often based on extrapolation from single case studies or case series. This retrospective study included 33 dogs and showed little improvement in median overall survival, but marked increase in toxicity.…”
mentioning
confidence: 99%